2009
DOI: 10.2106/jbjs.h.00246
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thrombin Activation of Platelet-Rich Plasma on Demineralized Bone Matrix Osteoinductivity

Abstract: Platelet-rich plasma significantly increased in vivo demineralized bone matrix osteoinductivity only when used without thrombin activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 38 publications
6
100
0
4
Order By: Relevance
“…Th is type of DBM has shown consistent composition and proven eff ectiveness in previous studies using a heterotopic bone formation model and an in vitro model. 173,317,318 Possibly, the natural circumstances of the joint (i.e., high loading forces and possible intrusion of fl uid into the OCD) might preclude the eff ectiveness of the DBM in the present study. Remnants of the DBM were found in two specimens, suggesting not all the material had remodeled.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Th is type of DBM has shown consistent composition and proven eff ectiveness in previous studies using a heterotopic bone formation model and an in vitro model. 173,317,318 Possibly, the natural circumstances of the joint (i.e., high loading forces and possible intrusion of fl uid into the OCD) might preclude the eff ectiveness of the DBM in the present study. Remnants of the DBM were found in two specimens, suggesting not all the material had remodeled.…”
Section: Discussionmentioning
confidence: 87%
“…85,234,399 Th ese joints might thus not be reliably compared in osteochondral defect healing models. In general, the eff ectiveness of DBM depends on numerous variables, including the age of the donor, 347 the tissue bank and the lot, 172,173,450 prolonged heat treatment, 196 the size or shape of the graft particles, 155 the nature of the carrier material, the extent of residual bone mineral content, 459 and the method of sterilization. 171 However, most of these variables are not applicable to the commercially available DBM used in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to PPP and FCS, stimulation with PRP resulted in highest proteoglycan and collagen synthesis, whereas most of the collagen was identified as collagen type II. Spreafico et al (2009) Han et al (2009) showed that thrombin activation eliminates the chondroand osteoinductive potential of PRP. Two other studies (Doucet et al, 2005;Zaky et al, 2008) strengthen these results, reporting successful chondrogenic induction of BMSC; in fact, they did not apply thrombin but used several freeze-thaw cycles to activate PRP.…”
Section: The Underlying Effect Of Platelet-derived Products: Knowledgmentioning
confidence: 99%